Methodology for the selection of financial indicators in the area of information and communication activities - Milichovský, František; Hornungová, Jana (Business: Theory and Practice, 2013)
The article presents issues of performance measurement. Currently, the performance plays an important role in management of companies. Usually, it could be defined as a system that uses the information to produce the appropriate changes in organizational culture, systems and processes to achieve optimal performance agreement targets, allocation of resources, information management on possible modifications of business strategy or sharing the results continued individual goals. In many cases, the performance is very crucial competitive advantage in the market. Due the performance monitoring the companies can find the Key Performance Indicators, also known as KPIs that help to organization define and measure progress toward organizational goals. The main aim of the paper is to find which factors of corporate performance system are in Czech companies important. To find these factors was used theoretical information from the area of KPIs and data from primary research (questionnaire survey). This data are applied by statistical evaluation of selected indicators which can help determine the significance of the indicators in the monitored area.